Uso de lodo de esgoto como fonte alternativa de nitrogênio para o cultivo do tomateiro cereja (Lycopersicum esculentum sp.) - Dantas, Jolly Dayanne de Melo (2010)
The wastewater treatment is necessary to reduce the impact of river pollution in large cities. This treatment is generated a large amount of organic matter decanted, called sludge. In order to make use of organic waste and consolidate a model of sustainable agriculture, that has been employing throughout the world, the use of sewage sludge on farmlands. Organic fertilization has been commonly practiced as a source of nutrients, among them nitrogen, to attend the nutritional needs of tomato. This study evaluates the effectiveness of using sewage sludge by Station Treatment of Housing Journalist Orlando Dantas, from Companhia de Saneamento de Sergipe - DESO that is considered a domestic sewage, as a source of nitrogen for growth and yield of tomato cherry on Cambisoil, traditionally present in farmlands of Sergipe, and more studying the implications of its use in the physiology of tomato. The experiment was conducted in greenhouse located in the Biology Department (UFS), São Cristóvão / SE. The experimental design was completely randomized design with five treatments and five replications and two plants. The treatments were a combination of soil and increasing dosages of sewage sludge as the amount of available nitrogen in sewage sludge as also by the amount of N recommended for growing tomatoes. The treatments were T1: mineral fertilization, T2: no fertilization, T3: ½ sludge dose, T4: 2.0 sludge dose, T5: 4,0 sludge dose, considering the quantity of avalaible nitrogen on sludge, and also, N recommended to tomato cultivation. The growth of plants were determined by dry mass of roots and shoots of plants, number and fruit weight, root length. Variables such as net photosynthesis (A), stomatal conductance (gs), transpiration (E) and internal CO2 concentration (Ci) were made when the plants started flowering. There was greater root growth at T2 if compared to other treatments. For root, leaf, stem, shoot and total dry weight there were beneficial effect of sludge in relation to control. Regarding the number of fruit and tomato production, they were higher when there was organic fertilization, demonstrated the capacity of replaceable of this residue as a mineral fertilizer. There was effect in the variables of stomatal conductance and net photosynthesis at the rate of 2.0 mg dm-3 sludge showed the best response. As to the internal carbon concentration in leaves and photosynthesis rate, these parameters had an inversely proportional relationship and these variables are associated to photosynthesis activity. The case study leads us to consider a dose of 2.0 mg dm-3 the best for cherry tomato under greenhouse conditions. There was effect in the variables of stomatal conductance and net photosynthesis at the rate of 2.0 mg.dm-3 sludge showed the best response. As to the internal carbon concentration in leaves and photosynthesis rate, these parameters had an inversely proportional relationship and these variables are associated to photosynthesis activity. The case study leads us to consider a dose of 2.0 mg dm-3 the best for cherry tomato under greenhouse conditions.